2018
DOI: 10.1080/19476337.2018.1518344
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement of half-smooth tongue sole (Cynoglossus Semilaevis) fillets by chitosan coatings containing rosmarinic acid during storage

Abstract: The effects of chitosan edible coating incorporated with rosmarinic acid on the quality of half-smooth tongue sole fillets were examined during 18 days of refrigerated storage (4 ± 0.5°C). The samples were analyzed by physicochemical, microbiological, and sensory characteristics. Results showed that samples coated with 1% chitosan containing 30 or 40 mg/L rosmarinic acid significantly lower the total volatile basic nitrogen, K value, free fatty acids, trimethylamine, total viable counts, and H 2 S-producing ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…FAAs are precursors of volatile flavor compounds and are responsible for flavor development during storage [56]. In the present research, most of the FAAs showed upward trends in all Chinese sea bass samples during superchilling storage at −0.9 • C ( Table 1).…”
Section: Free Amino Acids (Faas)valuessupporting
confidence: 53%
“…FAAs are precursors of volatile flavor compounds and are responsible for flavor development during storage [56]. In the present research, most of the FAAs showed upward trends in all Chinese sea bass samples during superchilling storage at −0.9 • C ( Table 1).…”
Section: Free Amino Acids (Faas)valuessupporting
confidence: 53%
“…FAAs are precursors of volatile flavor compounds and responsible for flavor development (Li, Mei, Shen, & Xie, ). In the present research, most of FAAs and total FAAs showed upward trends in all samples during cold storage (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine triphosphate (ATP) and its degradation products (adenosine diphosphate (ADP), adenosine monophosphate (AMP), IMP, HxR and Hx) in turbot samples were determined by a RP-HPLC procedure proposed by Li et al [ 37 ]. After obtaining all of the ATP metabolites from HPLC, the freshness index K value was calculated as follows: …”
Section: Methodsmentioning
confidence: 99%